Pembelajaran Matematika Berbasis Aplikasi Google Classroom pada Materi Bangun Ruang Sisi Datar Green Industry di SDN Cengkareng 11 - Putri Amanah; Risyda Zulfa; Ina Magdalena (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
This study aims to analyze the effectiveness of mathematics learning through the Google Classroom application on the topic of three-dimensional shapes at SDN Cengkareng 11. The background of this research is the transition from face-to-face learning to online learning due to the COVID-19 pandemic and government policies to ensure safe distance learning. This research employed a qualitative method with data collected through interviews, open-ended questionnaires, and documentation. The subjects consisted of five students and one mathematics teacher. The findings show that in the planning stage, the teacher prepared lesson plans, learning media, and relevant teaching materials. During the learning process, Google Classroom facilitated interaction, task submission, and access to learning resources. In the evaluation stage, students’ learning outcomes reached an average score of 67.6, all students achieved the school’s minimum mastery criteria, and responses indicated that the application was effective. Thus, the use of Google Classroom in mathematics learning on three-dimensional shapes has been proven effective in supporting the achievement of learning objectives.